Temporal Changes in Periprocedural Events in the Carotid Revascularization Endarterectomy Versus Stenting Trial. Issue 8 (August 2015) - Howard, George; Hopkins, L. Nelson; Moore, Wesley S.; Katzen, Barry T.; Chakhtoura, Elie; Morrish, William F.; Ferguson, Robert D.; Hye, Robert J.; Shawl, Fayaz A.; Harrigan, Mark R.; Voeks, Jenifer H.; Howard, Virginia J.; et al.
Abstract : Background and Purpose—: Post-hoc, we hypothesized that over the recruitment period of the Carotid Revascularization Endarterectomy Versus Stenting Trial (CREST), increasing experience and improved patient selection with carotid stenting, and to a lesser extent, carotid endarterectomy would contribute to lower periprocedural event rates. Methods—: Three study periods with approximately the same number of patients were defined to span recruitment. Composite and individual rates of periprocedural stroke, myocardial infarction, and death rate were calculated separately by treatment assignment (carotid stenting/carotid endarterectomy). Temporal changes in unadjusted event rates, and rates after adjustment for temporal changes in patient characteristics, were assessed. Results—: For patients randomized to carotid stenting, there was no significant temporal change in the unadjusted composite rates that declined from 6.2% in the first period, to 4.9% in the second, and 4.6% in the third ( P =0.28). Adjustment for patient characteristics attenuated the rates to 6.0%, 5.9%, and 5.6% ( P =0.85). For carotid endarterectomy–randomized patients, both the composite and the combined stroke and death outcome decreased between periods 1 and 2 and then increased in period 3. Conclusions—: The hypothesized temporal reduction of stroke+death events for carotid stenting–treated patients was not observed. Further adjustment for changes in patient characteristics between periods, including the addition of asymptomatic patients and a >50% decrease in proportion of octogenarians enrolled, resulted in practically identical rates. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00004732. Abstract : Supplemental Digital Content is available in the text.